(untitled) (Journal of Open Law, Technology & Society, 2013)
The idiom of both the General Public License and the Lesser General Public License seem to be grounded in the C programming language. This article analyzes the Lisp Lesser General Public License (colloquially and here referred to as the “LLGPL”), a specific attempt to apply the LGPL to a language with a programming paradigm and method of building and distributing programs that traditionally differs substantially from the approach of C. In addition, this article attempts to understand whether the LLGPL actually succeeds in its stated goal of translating the LGPL to the Lisp context or whether the LLGPL changes the requirements and philosophical moorings of the LGPL.